Interplay of Digital Financial Inclusion, Technological Innovation, Good Governance, and Carbon Neutrality in the Top 30 Remittance-Receiving Countries: The Significance of Renewable Energy Integration - Farzana, Nusrat; Qamruzzaman, Md; Mindia, Piana Monsur (International Journal of Energy Economics and Policy, 2024)
Our research explores the nexus between digital finance inclusion, technological innovation, good governance, renewable energy, and carbon neutrality in the top 30 remittance-receiving countries, focusing on the period from 2001 to 2020. Through comprehensive panel data analysis employing SH tests, CSD tests, CADF tests, D-H causality tests, and robustness checks, we investigate the impacts of these factors on carbon emissions. This study uncovers a positive relationship between digital financial inclusion and reduced carbon emissions, suggesting that access to digital finance can significantly lower carbon footprints. This aligns with prior research indicating that digital finance mitigates the need for traditional banking and paper transactions, thus contributing to environmental sustainability. We also find that remittances have a beneficial impact on carbon neutrality efforts, as they often fund investments in clean energy technologies and sustainable development initiatives. However, the expansion of digital financial services has been linked to increased energy consumption and electronic waste, highlighting the complexity of its environmental impact. Furthermore, our findings underscore the critical role of effective governance in achieving carbon emission reduction goals. Countries with transparent, accountable, and efficient governance systems tend to implement ambitious climate policies successfully. Additionally, technological innovation emerges as a pivotal factor in transitioning to a low-carbon economy, with innovation in clean energy technologies playing a significant role in reducing carbon emissions. Our analysis reveals strong positive correlations among digital finance, remittances, technological innovation, good governance, renewable energy, and carbon neutrality. The study suggests several policy recommendations to enhance sustainability and reduce carbon emissions. These include investing in renewable energy, improving governance practices, leveraging digital financial services and remittances for sustainable development, and fostering global collaboration. By implementing these strategies, countries can make significant strides toward environmental sustainability and carbon neutrality. This research contributes valuable insights into the interconnectedness of digital finance, remittances, governance, innovation, renewable energy, and carbon emissions. It offers guidance for policymakers and stakeholders on crafting effective strategies for sustainable economic development and environmental protection, emphasizing the importance of an integrated approach to achieve global carbon neutrality goals.